Evolution by Association : a History of Symbiosis. - Sapp, Jan (Oxford University Press, 1994)
1. Symbiosis: Evolution in Action2. The Messages of Mutualism3. Socially Constructing the Individual4. The Mystical Foundations of Symbiogenesis in Russia5. Gaia and WWI British Genesis Stories6. Germ Theory and Les Symbiotes in France7. The Pasteurization of Les Symbiotes8. Les Symbiotes Revisited9. Illusory Anthropomorphism and Verbal Phantoms10. Organismic Boundaries and Disciplinary Demarcation11. Molecular Reconstruction12. The Dull Edge of Ockham's Razor13. Is Nature Really Motherly?Concluding Remarks.